Tabir Waktu dalam Kesibukan: Studi Hadis - Muhammad `Restu Alfansury; Gustiana Isya Marjani; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about time management. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about time management in the history of Ahmad No. 18251. The results and discussion of this study indicate that the status of the hadith regarding quality time management hasan li ghairihi with maqbul ma'mul bih qualifications for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 18251 gives a message that there is no need for mental health, healing, me time, and mindfulness if humans can uncover the veil of time that is really very busy in today's digital transformation era, this confirms how hadith provides valuable information for living life in the contemporary era.